“It Was Useless”: Emotional Geography of Pre-Service Teachers in The Online Teaching Practicum during COVID-19 Pandemic - Chandra, Dian Eka; Jayanti, Fernandita Gusweni; Iskhak; Angraini, Ria (UNIB Press, 2025)
This present study aims to explore emotional geographies of pre-service teachers in an online teaching practicum program conducted during the COVID-19 pandemic. Following the narrative study design, the present study employed video-stimulated recall interviews and reflective journals to collect the data. The data gained from 8 participants was then analyzed by following Hargreaves’ framework of emotional geography. It was found that the pre-service teachers experienced both distance and closeness in the five areas of emotional geography. It was also revealed that the dynamic of the distance and closeness influenced some aspects of the pre-service teachers’ pedagogical competence.